2016
DOI: 10.1097/mog.0000000000000261
|View full text |Cite
|
Sign up to set email alerts
|

Cause and management of muscle wasting in chronic liver disease

Abstract: Purpose of review Sarcopenia or loss of skeletal muscle loss is the major component of malnutrition and occurs in the majority of patients with liver disease. Lower muscle contractile function also contributes to the adverse consequences of sarcopenia. There are no effective therapies to prevent or reverse sarcopenia in liver disease. This review will discuss the advances in diagnosis, pathogenesis and treatment options for sarcopenia in liver disease. Recent findings Sarcopenia increases mortality, risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 46 publications
5
88
0
3
Order By: Relevance
“…The current study revealed that ammonia‐induced up‐regulation of myostatin and the consequent decreased protein synthesis are partially reversible in vitro and in vivo . Increased myostatin expression was not fully reversed by ammonia‐lowering therapy, which may be due to incomplete reduction in muscle ammonia concentrations or additional ammonia‐independent mechanisms of myostatin regulation in vivo . Targeting ammonia alone may also not be adequate to reverse myostatin expression as our in vitro data suggest that after 48 hours of ammonia withdrawal there is nearly complete reversal of the molecular perturbations but that in vivo ammonia reduction does not completely reverse these alterations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The current study revealed that ammonia‐induced up‐regulation of myostatin and the consequent decreased protein synthesis are partially reversible in vitro and in vivo . Increased myostatin expression was not fully reversed by ammonia‐lowering therapy, which may be due to incomplete reduction in muscle ammonia concentrations or additional ammonia‐independent mechanisms of myostatin regulation in vivo . Targeting ammonia alone may also not be adequate to reverse myostatin expression as our in vitro data suggest that after 48 hours of ammonia withdrawal there is nearly complete reversal of the molecular perturbations but that in vivo ammonia reduction does not completely reverse these alterations.…”
Section: Discussionsupporting
confidence: 90%
“…Despite compelling evidence that hyperammonemia induces skeletal muscle metabolic and molecular perturbations, it is not known if lowering ammonia will reverse these responses and consequent sarcopenia. Current options to reverse sarcopenia have focused on nutritional and amino acid supplementation, with limited benefits …”
mentioning
confidence: 99%
“…However, in the present study, the positive predictive value of SARC‐F‐J was higher, whereas the negative predictive value was lower compared with previous studies. In patients with chronic liver disease, muscle atrophy due to physiological aging, increase in inflammation and oxidative stress, diet low in protein and energy, myostatin, decline in branched‐chain amino acids, hyperammonemia, cachexia, and other factors may lead to sarcopenia. Thus, the prevalence of sarcopenia in patients with chronic liver disease may be higher than that observed in the general elderly population and patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions that focus only on deficiency replacement have generally been ineffective while targeted therapies have the potential to reverse muscle loss[1, 1820, 26, 66, 87]. The major strategies that have been used to improve muscle mass include supplemental calorie and protein intake, increased physical activity, supplemental hormone therapy, and mechanistic targeted treatments[17, 26, 109111]. The critical outcome measures include survival, hospitalization, quality of life, development of and recovery from other complications of cirrhosis.…”
Section: Management Strategiesmentioning
confidence: 99%